A new three-level indirect matrix converter with reduced number of switches - Klumpner, Christian; Lee, Meng Yeong; Pitic, Cristian; Wheeler, Patrick; Zanchetta, Pericle (2007)
Matrix converters are sine wave in/out forced commutated single-stage AC/AC direct frequency changers using a single bi-directional switch to connect any input to any output. Indirect two-stage matrix converters provide similar input and output performance with no passive component in the dc-link. The difference is that some of these topologies require less switching devices or are able to achieve multilevel output voltage capability. This paper proposes a new indirect matrix converter topology with a three-level phase to neutral output voltage capability and reduced number of devices. A new modulation scheme, simpler that a standard 3-level scheme, is proposed. The performance of the converter in terms of input and output waveform quality and power losses is evaluated through simulations and on an experimental prototype.